The ingenue : a novel - Kapelke-Dale, Rachel (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2022)
"My Dark Vanessa meets The Queen's Gambit in this new novel of suspense about the bonds of family, the limits of talent, the risks of ambition, and the rewards of revenge. When former piano prodigy Saskia Kreis returns home to Milwaukee after her mother's unexpected death, she expects to inherit the family estate, the Elf House. But with the discovery that her mother's will bequeathed the Elf House to a man that Saskia shares a complicated history with, she is forced to reexamine her own past--and the romantic relationship that changed the course of her life--for answers. Can she find a way to claim her heritage while keeping her secrets buried, or will the fallout from digging too deep destroy her? Set against a post #MeToo landscape, Rachel Kapelke-Dale's The Ingenue delves into mother-daughter relationships, the expectations of talent, the stories we tell ourselves, and what happens when the things that once made you special are taken from you. Moving between Saskia's childhood and the present day, this dark, contemporary fairy tale pulses with desire, longing, and uncertainty, as it builds to its spectacular, shocking climax"--